An analysis of climate change and health hazards : results from an international study - Walter Leal Filho and Linda Ternova and Muhammad Muddassir Fayyaz and Ismaila Rimi Abubakar and Marina Kovaleva and Felix Kwabena Donkor and Samuel Weniga Anuga and Abraham R. Matamanda and Ilija Djekic and Ibrahim Abatcha Umar and Felicia Motunrayo Olooto and Maria Meirelles and Gustavo J. Nagy and Julia May and Marta May and Eromose Ebhuoma and Halima Begum (International journal of climate change strategies and management, 2022)
Purpose: The interconnections between climate change and health are well studied. However, there is a perceived need for studies that examine how responses to health hazards (e.g. cardiovascular diseases, ozone layer effects, allergens, mental health and vector-borne diseases) may assist in reducing their impacts. The purpose of this paper is to review the evidence on health responses to climate hazards and list some measures to address them. Design/methodology/approach: A mixed literature review, bibliometric analysis and an original online survey were undertaken on 140 participants from 55 countries spread across all geographical regions. Findings: The bibliometric analysis identified that most climate-related health hazards are associated with extreme weather events. However, only one-third of the investigated papers specifically analysed the connections between climate change and health hazards, revealing a thematic gap. Also, although Africa is highly affected by climate change, only 5% of the assessed studies focused on this continent. Many respondents to the survey indicated “heat distress” as a significant vulnerability. The survey also identified social determinants relevant to climate-induced health vulnerabilities, such as socioeconomic and environmental factors, infrastructure and pre-existing health conditions. Most respondents agree that policies and regulations are the most effective adaptation tools to address the public health hazards triggered by climate change. This paper presents some suggestions for optimising public health responses to health hazards associated with climate change, such as the inclusion of climate-related components in public health policies, setting up monitoring systems to assess the extent to which specific climate events may pose a health threat, establishing plans to cope with the health implications of heatwaves, increased measures to protect vulnerable groups and education and awareness-raising initiatives to reduce the overall vulnerability of the population to climate-related health hazards. These measures may assist the ongoing global efforts to understand better – and cope with – the impacts of climate change on health. Originality/value: The combination of a literature review, bibliometric analysis and an original world survey identified and presented a wide range of responses.
Keywords: Adaptation responses; Bibliometric analysis; Climate change; Climate change responses; Extreme weather; Health hazards